Performansi Membran Polyvinylidene Fluoride (PVDF) dengan PVA dan Variasi Konsentrasi Zif-8 Untuk Antibakteri dan Removal Kekeruhan - Aizatun Fadilah (Fakultas Teknik, 2026)
One of the water quality parameters is turbidity caused by pollution from domestic and non domestic activities. Polyvinylidene Fluoride (PVDF) membrane technology is used in water treatment, but its hydrophobic properties cause biological fouling that affects membrane performance. Modification of PVDF with ZIF-8 and PVA can improve the hydrophilic properties of the membrane. The purpose of this study is to determine the effect of varying ZIF-8 concentrations and PVA immersion time on antibacterial and turbidity removal, in addition to membrane flux. Membrane modification was performed using the Non-Solvent Induced Phase Separation (NIPS) PVDF/ZIF-8 method, with DMAc as the solvent and distilled water as the non-solvent, and the PVA coagulation bath method. Characterization of membranes using Scanning Electron Microscope Energy Dispersive X-ray (SEM EDX) to analyze the morphology and constituent elements of membranes, as well as Fourier Transform Infrared Spectroscopy (FTIR) to identify membrane functional groups. Membrane performance was evaluated through antibacterial tests on Escherichia coli and Bacillus subtilis bacteria as antibacterial indicators, as well as turbidity tests using a standard solution of 50 NTU. The results showed that the addition of ZIF-8 and PVA successfully modified the PVDF membrane without damaging or removing its basic chemical structure. The best antibacterial test value was found in the 0.5 wt% ZIF-8 variation and 30 minutes PVA immersion time, with a clear zone value of 6.8 mm for Escherichia coli bacteria and 10 mm for Bacillus subtilis bacteria. The highest turbidity removal efficiency value was found in the 0.5 wt% ZIF-8 variation and 30 minutes of PVA immersion time, at 91.7%. The lowest turbidity removal efficiency value was found in the 7 wt% PVDF control variation, at 59%. The highest flux value on the PVDF membrane with ethanol pre-wetting was at 10 minutes, which was 226,45 𝐿/𝑚2.ℎ
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi